Blended e-Learning: Alternatif Model Pembelajaran Jarak Jauh di Indonesia - Soekartawi Soekartawi (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2006)
Indonesia, with more than 220 million people spreading in the more than 17 thousand islands, is facing big problem associated with providing educational opportunities for people in the country. To solve this problem, the Government established the Education Law (UU No 20/2003, i.e. SISDIKNAS). Through this Law, and also recognizing the advantages of IT/ICT, the Government has given an opportunity to all education institutions to maximize the use of IT/ICT for running distance learning (DL). Consequently, many education institutions have been working hard for the last few years to develop policies and strategies for education to infuse technology for searching appropriated models for executing distance learning (DL).Recognizing the advantages of DL, and to make DL models more efficiently, people has tried to develop various DL models. One of newest models is called ‘Blended e-Learning’ (BEL). The model, BEL, is designed basically based on combination of the best aspects of application of information technology e-Learning, structured face-to-face activities, and real world practice. BEL approach uses the strengths of each to counter the other’s weaknesses. The obvious advantage of BEL solution is that learning becomes a process, rather than an event. This is because BEL puts training into job environment and provides a forum for every learning style to gain maximum results.To make BEL more effective, there are six steps that shall be followed, i.e. (a). Identify the content and convert to online delivery, (b). Design the blended learning solution, (c) Have the online content formatted and hosted, (d). Test the design, (e). Publicize and run the blended course and (f). Set up criteria for evaluating learning technology.This article reviews and reveals what makes BEL model so powerful, and choose the right mix of delivery methods for the best blend of skill enhancement and sustainability to ensure long-term competitive advantageKata kunci: Distance Learning (DL), Application of IT/ICT in DL, Blended e-Learning